Técnicas de expresión corporal para desarrollar el autoestima en los niños y niñas de educación inicial de 4 años de la escuela fiscal “Rosa Zárate” del cantón Salcedo provincia Cotopaxi, durante el periodo académico 2014-2015 - Borja Tercero, Silvia Angelica (2015)
This research was designed in order to get the teachers, parents‟ awareness on the body language importance and the benefits to be gained through the methodological guide for the self-esteem development in the school students. The proposal‟ relevant value is to be a tool for teaching and learning children. This is an innate ability that allows the child to discover the world leading to the game development. This research was a contribution to children, teachers, parents and director to "Rosa Zarate Statal School. The technique applied for data collection was survey. Also, the instruments were: questionnaire, interview and checklist. To analyze the information obtained. The percentage statistical analysis was performed to analyze the information obtained. The result was that body language which is significant in the self-esteem development process. It allows to child to feel confident as well be motivated to face their fears and communicate with others.